2019
DOI: 10.3390/ma12203299
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Static and Dynamic Mechanical Behavior for Dry and Saturated Cement Mortar

Abstract: Deformational and breakage behaviors of concrete and cement mortar greatly influence various engineering structures, such as dams, river bridges, ports, tunnels, and offshore rig platforms. The mechanical and petrophysical properties are very sensitive to water content and are controlled by the liquid part in pore spaces to a large extent. The objective of this paper is to investigate the water saturation effect on the strength characteristics and deformability of cement mortar under two loading conditions, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This observation might suggest that the water-to-cement ratio is insufficient to completely understand the effect of water saturation on the properties of concrete. The decrease in strength can be explained by several factors as explained by previous studies [ 2 , 19 , 21 , 26 , 43 , 51 , 52 , 53 ]. One interpretation is from the standpoint of energy [ 19 , 21 , 23 , 51 , 53 ].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This observation might suggest that the water-to-cement ratio is insufficient to completely understand the effect of water saturation on the properties of concrete. The decrease in strength can be explained by several factors as explained by previous studies [ 2 , 19 , 21 , 26 , 43 , 51 , 52 , 53 ]. One interpretation is from the standpoint of energy [ 19 , 21 , 23 , 51 , 53 ].…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, it has been demonstrated by previous researchers that the increasing moisture content (or water saturation level) affects the static properties of concrete and P-wave velocity of concrete in different ways. Some researchers corroborated that the compressive strength decreases as the saturation level increases [ 1 , 19 , 20 , 21 , 22 , 23 ]. Some researchers [ 1 , 20 , 23 , 24 ] observed that the modulus of elasticity increased when the saturation increases while others [ 25 , 26 ] have observed that elastic modulus decreased as the saturation increases.…”
Section: Introductionmentioning
confidence: 98%
“…There has been extensive research on the interaction between water and rocks, focusing primarily on the following aspects: microstructural evolution of rocks under water-rock interactions [4][5][6][7], the static mechanical behavior of rocks under water-rock interactions [8][9][10][11], the dynamic behavior of rocks under water-rock interactions [8,12,13], and the physical and chemical interaction mechanisms between water and rocks [2,14,15]. It can be concluded that the presence of water to some extent disrupts the macroscopic and mesoscopic structure of rocks, weakening the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%